Entities obligated and authorized to raise a child under the 1983 Code of Canon Law - Czuba, Roksana Patrycja (Prawo Kanoniczne, 2020)
The article includes considerations about the entities obliged and entitled to raise a child on the basis of the Code of Canon Law of 1983 in force. The aim of the article is to familiarize the reader with a given topic by analyzing the code norms and indicating which entities are responsible for the child's educational process. At the outset, attempts were made to define the term "child". The ecclesiastical legislator by "child" means a minor before the age of seven who does not have the ability to act rationally. Other definitions are presented in the pedagogical dictionary, contrary to the teaching of the Church. In Polish law, the legal definition is presented in the Act on the Ombudsman for Children, on the basis of which, a child is every human being from conception to the age of majority. The term "upbringing" was successively specified, indicating secular definitions. The last part will concern the main analysis of code norms referring to entities responsible for the upbringing of a child. Parents are indicated here as the basic social unit, fulfilling the duties of parents with the help of state authorities, the church and the school. The whole discussion will end with a summary, which will include conclusions de lege lata and de lege feranda based on the analyzed documents of Magisterium Ecclesiae.